The Role of The Notary to Prevent Money Laundering Actions - I Made Pria Dharsana; Indrasari Kresnadjaja (Community Service Journal of Law, 2023)
The role of a notary in preventing money laundering is by reporting to the PPATK when he finds out that there is a suspicious financial transaction in connection with the deed he made. The position of a Notary as a reporter in the event of a suspicious financial transaction as an effort to prevent money laundering does not violate the principle of confidentiality of office, instead it is an obligation for the Notary in applying the precautionary principle. The notary as the reporting party is an implementation of his obligations regulated in UUJN Article 16 paragraph (1) point a, namely acting in a trustworthy and honest manner. Notaries are appointed by the State to serve the public in the field of civil law, therefore the Notary must also take care that the State is not harmed by efforts to disguise the proceeds of crime, hereby the Notary is subject to higher interests. This is intended so that the Notary does not get involved in money laundering cases, because they are considered to have contributed to the commission of a crime.